2021
DOI: 10.1101/2021.03.23.21253487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired immune signaling and changes in the lung microbiome precede secondary bacterial pneumonia in COVID-19

Abstract: Secondary bacterial infections, including ventilator associated pneumonia (VAP), lead to worse clinical outcomes and increased mortality following viral respiratory infections. Critically ill patients with coronavirus disease 2019 (COVID-19) face an elevated risk of VAP, although susceptibility varies widely. Because mechanisms underlying VAP predisposition remained unknown, we assessed lower respiratory tract host immune responses and microbiome dynamics in 36 patients, including 28 COVID-19 patients, 15 of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated a significantly higher incidence of VA-LRTI and notably VAP in SARS-CoV-2 pneumonia patients versus non-SARS-CoV-2 pneumonia patients [ 5 , 8 – 10 ]. High rates of ARDS, alveolar inflammation, prolonged IMV, lung microbiota alteration, COVID-19-related specific lesions, neuromuscular blocking and immunosuppressive agent use could explain this high rate of VAP in SARS-CoV-2 pneumonia patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated a significantly higher incidence of VA-LRTI and notably VAP in SARS-CoV-2 pneumonia patients versus non-SARS-CoV-2 pneumonia patients [ 5 , 8 – 10 ]. High rates of ARDS, alveolar inflammation, prolonged IMV, lung microbiota alteration, COVID-19-related specific lesions, neuromuscular blocking and immunosuppressive agent use could explain this high rate of VAP in SARS-CoV-2 pneumonia patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the lung microbiota community was found to be due to the overgrowth of the opportunistic pathogens in patients developing VAP compared to the critically ill patients without VAP (Tsitklis et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with BSIs had significantly longer hospitalizations, higher ICU admission and mortality rates compared to those without BSIs [ 13 • ]. Moreover, COVID-19-induced pathological processes such as accumulation of mucus, diffuse alveolar damage, impairment of immune signaling, and immune cell depletion may have facilitated the onset of SBIs and reduced the efficacy of drug treatment [ 7 , 19 , 20 ].…”
Section: Sbis In Covid-19 Patients: Why Is It a Challenge?mentioning
confidence: 99%